Cost-Benefit Analysis of Immigration Violations: A Case Study of 5 Indian Nationals Working on Visitor Visas in Jakarta - Rizal Chandrawinata; Margaretha Hanita; Nur Fatwa (Green Publisher Indonesia, 2026)
The misuse of visit stay permits for work by foreign nationals is a problem that has the potential to negatively impact the economic sector, particularly the collection of Immigration Non-Tax State Revenue (PNBP). This study aims to comprehensively analyze immigration violations and their enforcement against foreign nationals using a cost-benefit analysis approach. This study uses a case study of five Indian citizens working using visit stay permits in Jakarta. This study uses qualitative and quantitative approaches, collecting data from several sources, including analysis of policy documents, data on foreign nationals involved, and calculations of the resulting costs and benefits. The analysis shows that law enforcement is not yet effective enough against violators because it still causes economic impacts (losses in immigration non-tax revenue). Meanwhile, the only benefits obtained are forced removal of foreign nationals from Indonesian territory (deportation) due to immigration violations. This study recommends an immigration law enforcement strategy that emphasizes imposing costs on foreign nationals who violate their stay permits as an effort to recover the losses in immigration non-tax revenue. Therefore, the results of this study are expected to serve as a reference for policymakers in formulating more effective and sustainable immigration policies.